What is Driving Women's Financial Inclusion Across Countries? - Delechat, Corinne (IMF Working Papers; Working Paper, 2018)
Using a broad set of macroeconomic country characteristics to supplement a new and comprehensive micro-level dataset for 140 countries, we identify structural factors, policies, and individual characteristics that are associated with financial inclusion-in general, and for women in particular. We find that structural country characteristics, such as resource-richness and level of development, and policies, such as stronger institutions, and financial development are significantly related to financial inclusion. We find a robust negative relationship between being female and financial inclusion as in previous studies, and our analysis points to legal discrimination, lack of protection from harassment, including at the work place, and more diffuse gender norms as possible explanatory factors.